Comparison of Conventional Tube and Gel-Based Agglutination Tests for AB System Blood Typing in Cat - Spada, Eva; Perego, Roberta; Baggiani, Luciana; Proverbio, Daniela (Frontiers in Veterinary Science, 2020)
Gel technology is widely used for blood typing in human medicine. It has a number of advantages over routine tube testing, including: standardization, stability, smaller sample volume, ease of performance and analysis, and speed. The aim of this study was to evaluate feline blood typing using the gel column technique. TUBE agglutination typing was performed in 143 feline blood samples from blood donors and recipients, healthy and sick patients, and whole blood units anticoagulated with EDTA or CPDA. Plasma from type B cats was used as anti-A reagent, Triticum vulgaris lectin as anti-B reagent and the control was PBS. Agglutination in back typing of type B and AB samples with type A RBCs was used to confirm whether the samples were type B (presence) or type AB (absence). Blood typing in a neutral gel column technique (GEL) using the same anti-A and anti-B reagents was performed on duplicate samples. Sensitivity (Se), specificity (Sp), positive likelihood ratio (PLR), negative likelihood ratio (NLR), positive predictive value (PPV), negative predictive value (NPV), overall accuracy and Cohen’s kappa coefficient (K) for GEL were calculated, with TUBE considered the gold standard technique. Of 143 samples typed with TUBE, 98 (68.5%) were type A, 25 (17.5%,) type B and 20 (14.0%) type AB. Backtyping confirmed the categorization of all type B and AB samples. Of these samples gel testing produced 115 (80.4%) concordant results, a mixed-field agglutination pattern (layers of RBCs at both the top and at the bottom of the gel in either the A or B gel column) was seen in 27 samples and one type-B sample was misidentified as type-AB. If the mixed-field pattern was interpreted as a negative result 141/143 (98.6%) samples showed concordant results with an overall accuracy of the GEL of 100.00% for type-A, 98.93% for type-B, and 99.10% for type-AB. Strength of agreement was very good (K= 0.97). When the same anti-A and anti-B reagents are used, GEL is a sensitive and specific method for blood typing feline samples. Until additional studies have been performed, mixed-field patterns obtained in GEL testing should be classified as negative results.